2019
DOI: 10.3390/nano9070987
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Interactions between Benzo[a]pyrene and Fullerene (C60) in Toxicological Response of Marine Mussels

Abstract: This study aimed to assess the ecotoxicological effects of the interaction of fullerene (C60) and benzo[a]pyrene (B[a]P) on the marine mussel, Mytilus galloprovincialis. The uptake of nC60, B[a]P and mixtures of nC60 and B[a]P into tissues was confirmed by Gas Chromatography–Mass Spectrometry (GC–MS), Liquid Chromatography–High Resolution Mass Spectrometry (LC–HRMS) and Inductively Coupled Plasma Mass Spectrometer (ICP–MS). Biomarkers of DNA damage as well as proteomics analysis were applied to unravel the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 119 publications
7
32
0
Order By: Relevance
“…Risks to health as a result of exposure to nanomaterials, other than combustion particulates, are still largely unknown, although considerable concern has been expressed as to the safety of engineered nanomaterials. 31 , 39 , 83 , 126 Furthermore, there is now some evidence that engineered nanoparticles (eg, C 60 fullerene and glass nanofibres) can inhibit mTORC1, induce augmented autophagy, and some may even induce pathological dysfunctional autophagy 21 , 24 , 31 , 108 ; and these materials are finding their way into the environment and may impact on animal and human food networks and possibly on human health. 127 …”
Section: Hormesis and Autophagy In Animal And Human Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risks to health as a result of exposure to nanomaterials, other than combustion particulates, are still largely unknown, although considerable concern has been expressed as to the safety of engineered nanomaterials. 31 , 39 , 83 , 126 Furthermore, there is now some evidence that engineered nanoparticles (eg, C 60 fullerene and glass nanofibres) can inhibit mTORC1, induce augmented autophagy, and some may even induce pathological dysfunctional autophagy 21 , 24 , 31 , 108 ; and these materials are finding their way into the environment and may impact on animal and human food networks and possibly on human health. 127 …”
Section: Hormesis and Autophagy In Animal And Human Evolutionmentioning
confidence: 99%
“…8,32,69,81,82 Calabrese et al 68 and Zimmermann et al 8 have postulated that cells and organisms, preconditioned by exposure to mild stress, are protected against more harmful levels of stress and that the relevance of hormesis for both human pathophysiology and specific disease treatment is being increasingly recognized. 83 These authors have argued that this evolutionarily conserved process, hormesis, is directly linked to the capability to cope with pathological conditions, including aging and age-related diseases. They have also identified lysosomally mediated autophagy as a key component of this cytoprotective process.…”
Section: Role Of Autophagy and Hormesis In Disease And Agingmentioning
confidence: 99%
“…were also exposed to C 60 at 0.01, 0.1, and 1 mg/l concentration for 72 h. Later, the accumulation of C 60 in the digestive gland was demonstrated to induce dephosphorylation of mTOR with no oxidative stress for cellular distribution of C 60 at 0.01 mg/l concentration. The study suggested that mussels' most affected functions were related to the organization of the cytoskeleton, energy metabolism, and lysosomal activity [36,37]. Lastly, in another report on Mytilus galloprovincialis, the mussels were exposed to C 60 (0.01, 0.1, and 1 mg/l), B[a]P (5, 50, and 100 μg/l), and B[a]P (5, 50, and 100 μg/l) in combination with C 60 (1 mg/l).…”
Section: Interaction Of Fullerene With Aquaticmentioning
confidence: 99%
“…The study supports the hypothesis of an interaction between these two compounds and demonstrated an antagonistic relationship at the genotoxic and proteome expression level. However, as this effect is observed on a single concentration, the research group further suggested that other dosage concentrations should also be investigated [37,38].…”
Section: Interaction Of Fullerene With Aquaticmentioning
confidence: 99%
See 1 more Smart Citation